Top Management Support and Internal Auditor Competence as Determinants of Internal Audit Effectiveness: Evidence from Indonesian Public Higher Education Institutions - Fury Khristianty Fitriyah (CV Putra Publisher, 2026)
Internal audit effectiveness is central to organizational governance, accountability, and risk management in Indonesian public higher education institutions (HEIs). Despite its strategic importance, empirical evidence isolating the direct effects of top management support (TMS) and internal auditor competence (IAC) on internal audit effectiveness (IAE) without the confounding influence of mediating variables remains scarce in the Indonesian public sector context. Grounded in Resource-Based Theory (RBT), this study examines the direct relationships of TMS and IAC with IAE among 183 internal auditors from Autonomous Public HEIs (PTN-BH) and Public Service HEIs (PTN-BLU) in Indonesia, using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 4.0. The findings confirm that both variables exert statistically significant positive effects on IAE. Internal Auditor Competence emerges as the stronger predictor (β = 0.317, t = 4.354, p < 0.001), while Top Management Support also demonstrates a significant, albeit more modest, direct effect (β = 0.137, t = 1.973, p = 0.049). Together, these findings highlight that cultivating auditor competence and securing genuine managerial commitment are complementary and indispensable drivers of audit effectiveness in the Indonesian public HEI sector. The study contributes to the IA effectiveness literature by providing a focused, direct-effects model that disentangles the independent contributions of organizational support and human capital quality.